Custom Institutions as Drivers of Community Participation of Agricultural Society: Perspective of Sociology - Bahri, Syamsul; Juharni, Juharni; Syafri, Syafri; Burchanuddin, Andi; Asmirah, Asmirah; Nonci, Nurmi; Maidin, Rusdi; Iskandar, Iskandar; Harifuddin, Harifuddin (Technium Social Sciences Journal, 2023)
The existence of custom institution is associated with traditional community entities that are generally located in inland areas. Traditional society is a term that is attached because almost all the daily activities is simple of many people use local resources and the nature. The livelihoods of people are still dependent on agricultural land, plantations and forest products. In this context, custom institutions exist that ensures all kinds of community relations between them, the environment, and God to keep them in harmony. This paper intends to reveal the existence of custom institutions as a special community that called ‘Tau Appa’ in Maiwa Subdistrict. So that, explorative research is conducted by interviews and documentation studies. Interviews conducted with local community leaders and community members. The results of the research obtained as follows: (1) custom institution ‘Tau Appa’ is a manifestation of local trust of to Manurung. (2) ‘Tau Appa’ present to maintain life harmonization of local community. (3) people participation is divided into 2 types, namely custom participation, and development participation. (4) it needs the government support in strengthening the existence of custom institution. Observing that results, it can be concluded the following things: custom institution is the source of custom and social norms for the Matakali people, custom institution as the mobilizer of all people activities, custom institution need to be supported the existence, role and function by government.